Design tradeoffs and challenges in practical coherent optical transceiver implementations - Morero, Damián Alfonso (2016)
This tutorial discusses the design and ASIC implementation of coherent optical transceivers. Algorithmic and architectural options and tradeoffs between performance and complexity/power dissipation are presented. Particular emphasis is placed on flexible (or reconfigurable) transceivers because of their importance as building blocks of software-defined optical networks. The paper elaborates on some advanced digital signal processing (DSP) techniques such as iterative decoding, which are likely to be applied in future coherent transceivers based on higher order modulations. Complexity and performance of critical DSP blocks such as the forward error correction decoder and the frequency-domain bulk chromatic dispersion equalizer are analyzed in detail. Other important ASIC implementation aspects including physical design, signal and power integrity, and design for testability, are also discussed.